Experiences African domestic workers undergo as a result of sending their children to predominantly white schools - Mange, Nondwe Portia (Department of Psychology, 2014)
Sending African children to white schools brings about potential problems for all parties involved. However, the complications are more pronounced in situations where the child's mother is a domestic worker and the employer assumes an active role in the child's education. One such case triggered this research. Based on that particular case, the aim of this study was to explore experiences and feelings of African domestic workers with children in white schools.